1986
DOI: 10.1177/036354658601400617
|View full text |Cite
|
Sign up to set email alerts
|

Hook of the hamate fractures in athletes

Abstract: Five patients have been treated for six hook of the hamate fractures over the past 8 years by the authors. Of these, four patients were professional baseball players and one patient was an accountant. All fractures occurred while playing baseball; four while swinging a bat, and two secondary to a fall on an outstretched hand. Roentgenographic diagnosis was made by carpal tunnel view alone in two, oblique and carpal tunnel view in one, bone scan and subsequent carpal tunnel view in two, and computerized tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 25 publications
2
56
0
1
Order By: Relevance
“…Some authors (Watson and Rogers 1989) have recommended bone grafting for the treatment of the nonunion. However, we believe as other authors (Carter et al 1977, Stark et al 1977, Parker et al 1986, Smith et al 1988) that the entire hook should be resected at the base of the hamate as primary treatment.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Some authors (Watson and Rogers 1989) have recommended bone grafting for the treatment of the nonunion. However, we believe as other authors (Carter et al 1977, Stark et al 1977, Parker et al 1986, Smith et al 1988) that the entire hook should be resected at the base of the hamate as primary treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Fracture at the base of the hook of the hamate may not be quite as rare as previously assumed (Carter et al 1977, Stark et al 1977, Parker et al 1986, Smith et al 1988. The diagnosis may often be delayed because the signs and symptoms are rather non-specific, and routine radiography is not always diagnostic ( Norman et al 1985, Polivy et al 1985.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Halim & Weiss expected about 6 to 8 weeks after injury. 15,16 The palmar incision is sensitive for 4 to 6 weeks, and may benefit from desensitization before return to sport. 4 Athletes at the collegiate level can expect to have no change in sports performance compared with their baseline, and typically are satisfied with outcomes.…”
Section: Other Carpal Injuries Hook Of the Hamate Fracturesmentioning
confidence: 99%
“…The patient, now less focused on the elbow, reported that her ring and little fingers 'felt cold at times." Examination of the right hand revealed an abnormal resting finger position that consisted of clawing of the fourth and fifth fingers (6). Atrophy of the intrinsic hand muscles innervated by the ulnar nerve was noted.…”
Section: Case Reportmentioning
confidence: 99%